Numerical investigation of the effects of pitting corrosion on high-cycle fatigue of clinched joints - Chen, Chin; Harzheim, Sven; Hofmann, Martin; Wallmersperger, Thomas (Acta Mechanica)
Abstract The effects of corrosion on clinched joints are not completely understood yet. Recent research indicates that galvanic corrosion can actually enhance the fatigue life of clinched joints. It is then of significant interest to investigate the effects of another corrosion phenomenon, pitting corrosion, on the fatigue behavior of clinched joints. Pitting corrosion occurs in passive metals and can lead to stress concentrations. In the present study, the effects of pitting corrosion are investigated by using Lemaitre’s two-scale fatigue model with a 2D geometry of clinched joints. A slip condition is applied as a boundary condition to simplify the clinched joint model and reduce the computational cost of solving the contact mechanics problem. Additionally, a method to determine the damage strength and the damage exponent used in the two-scale damage model is introduced. Numerical simulations reveal that pitting corrosion reduces the fatigue life of clinched joints, particularly when it occurs on the internal surface in the neck area.

Numerical investigation of pitting corrosion in clinched joints - Harzheim, Sven; Chen, Chin; Hollmer, Katharina; Hofmann, Martin; Zimmermann, Martina; Wallmersperger, Thomas (Acta Mechanica)
Abstract The effect of corrosion on mechanically joined components is not well understood. While recent research shows that a brief exposure of clinched specimens to a salt spray environment improves the specimens’ fatigue life, other research shows a decrease in load bearing capabilities with increasing corrosion times. These studies primarily focus on galvanic corrosion. It is not entirely clear how other corrosion phenomena, such as pitting corrosion, affect the fatigue life of clinched joints. In this work, a numerical model is used, which is able to simulate corrosion pit growth in EN AW-6014. The experimental polarization data of EN AW-6014 are used directly in the calculation of the interface kinetics parameter of the model.

Influence of dispersion gas flow on the spray characteristics and γ-Fe2O3 nanoparticles formation and properties in reference SpraySyn burners - Massopo, Orlando; Tischendorf, Ricardo; Gonchikzhapov, Munko; Kasper, Tina; Augustin, Peter; Özer, Burak; Reddemann, Manuel; Kneer, Reinhold; Sheikh, Mohammed-Ali; Mert, Aydan Akyildiz; Wiggers, Hartmut; Schmid, Hans-Joachim (Powder Technology)
This study investigates the effect of dispersion gas (DG) flow on the formation and properties of maghemite (γ-Fe2O3) nanoparticles using standardized SpraySyn burners (SS1 and SS2). Several diagnostics were employed to characterize the spray and nanoparticles. Increasing DG flow (6 - 12 slm) results in smaller droplet sizes (DS), cooler flame temperatures, shorter high-temperature droplet/particle residence times, and smaller agglomerates in the size range of 5 - 12 nm with narrower primary particle size distribution, corresponding to higher mass fractal dimensions, as supported by TEM and SMPS analysis, resulting in more compact agglomerates. BET and TEM confirmed decreasing primary particle sizes with increasing DG flow. Raman and XRD analyses predominantly identified maghemite, which shows a bimodal distribution of crystallite sizes, while SS1 samples have a greater proportion of larger crystallites. The self-preserving size distributions of agglomerates with a geometric standard deviation of 1.5 are reached faster with increasing DG flow. The barrier effect of DG observed in SS1 leads to slower droplet combustion kinetics, higher temperatures, and delayed precursor release, which, along with downstream flow recirculation, result in significantly higher agglomeration rates outside the visible flame. SS2 demonstrates improved atomization, more stable flames, and finer, uniform nanoparticles with less carbonaceous residues (CR). Conversely, SS1 showed broader DS distributions and higher CR levels on the γ-Fe2O3 surface, especially at higher DG flow. This work highlights the essential role of DG flow and nozzle geometry in controlling droplet evaporation, flame stability, and nanoparticle growth, offering insights for optimizing SFS and validating numerical models.
Keywords: Spray flame synthesis; iron oxide nanoparticle; SpraySyn burner; Dispersion gas; Coaxial atomization; HiaT-SMPS

Quantitative holography for the characterisation of semiconductor amplifieres and lasers - Gerhardt, Nils Christopher; Hofmann, Martin R.; Zens, Leon; Möller, Jens; Besaga, Vira (Practical Holography XXXIX: Displays, Materials, and Applications)

Nontrivial $t$-designs in polar spaces exist for all $t$ - Weiß, Charlene (Des. Codes Cryptogr.)
A finite classical polar space of rank $n$ consists of the totally isotropic subspaces of a finite vector space over $\mathbb{F}_q$ equipped with a nondegenerate form such that $n$ is the maximal dimension of such a subspace. A $t$-$(n,k,λ)$ design in a finite classical polar space of rank $n$ is a collection $Y$ of totally isotropic $k$-spaces such that each totally isotropic $t$-space is contained in exactly $λ$ members of $Y$. Nontrivial examples are currently only known for $t≤ 2$. We show that $t$-$(n,k,λ)$ designs in polar spaces exist for all $t$ and $q$ provided that $k>\frac{21}{2}t$ and $n$ is sufficiently large enough. The proof is based on a probabilistic method by Kuperberg, Lovett, and Peled, and it is thus nonconstructive.

Laterally coupled vertical-cavity surface-emitting lasers with tunable resonance width and frequency - Lindemann, M.; D’Alessandro, M.; Ledentsov, N.; Makarov, O. Y.; Ledentsov, N. N.; Tibaldi, A.; Gerhardt, N. C.; Hofmann, M. R. (Journal of Applied Physics)

Efficient Online Automated Algorithm Selection in the Face of Data-Drift in Optimisation Problem Instances - Rook, Jeroen; Renau, Quentin; Trautmann, Heike; Hart, Emma (Proceedings of the 18th ACM/SIGEVO Conference on Foundations of Genetic Algorithms, FOGA 2025, Leiden, The Netherlands, August 27-29, 2025)

Die Möglichkeiten der Filament Extension Atomization - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim

Flow around Particles in Uniaxially Elongated Capillary Bridges - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim

Fließverhalten von unterschiedlichen Fluiden im Filament Extension Atomizer - Neudorf, Julian; Neukötter, Moritz

Boosting third-order nonlinearities in rutile TiO2 by chromium doping - Brinkmann, Marius; Meier, Falco; Spedt, Vladimir; Meier, Cedrik (Optics Express)
In this study, we investigate the impact of chromium-induced point defects on the nonlinear optical properties and electric-field-induced second harmonic generation (EFISH) in rutile titanium dioxide (TiO 2 ). Chromium thin films were deposited by electron beam evaporation on (001)-oriented bulk TiO 2 substrates and subsequently diffused into the lattice in a tube furnace under a nitrogen atmosphere at 900 °C. The introduction of chromium significantly enhanced the third harmonic generation (THG) of a 1560 nm laser, with an amplification factor of up to 8.3, indicative of an enhanced third-order nonlinear susceptibility, χ (3) . Moreover, the application of an external voltage induced a pronounced EFISH signal in the chromium-doped samples, further confirming the enhanced nonlinear response. These results demonstrate that defect engineering via chromium doping in rutile TiO 2 offers a promising pathway for the development of high-performance nonlinear optical devices.

What We Talk About When We Talk About K-12 Computing Education - Schulte, Carsten; Sentance, Sue; Sparmann, Sören; Altin, Rukiye; Friebroon-Yesharim, Mor; Landman, Martina; Rücker, Michael T.; Satavlekar, Spruha; Siegel, Angela; Tedre, Matti; Tubino, Laura; Vartiainen, Henriikka; et al. (2024 Working Group Reports on Innovation and Technology in Computer Science Education)

Surfacing Educational Traditions in European K–12 Computing Curricula: A Large-Scale NLP-Based Comparison - Sparmann, Sören; Altin, Rukiye; Mühling, Andreas; Schulte, Carsten (Proceedings of the 25th Koli Calling International Conference on Computing Education Research)

Rough Data in an Evolution System Generalizing 1D Thermoviscoelasticity with Temperature-Dependent Parameters - Winkler, Michael (Applied Mathematics & Optimization)

Special issue of Journal of Lie Theory dedicated to Karl-Hermann Neeb on the occasion of his 60th birthday (J. Lie Theory)

Modeling approaches for the decomposition behavior of preconsolidated rovings throughout local deformation processes - Gröger, Benjamin; Gerritzen, Johannes; Hornig, Andreas; Gude, Maik (Sheet Metal 2025)
This paper investigates two modeling approaches for the simulation of the deformation and decomposition behavior of preconsolidated rovings above the thermoplastic matrix{’} melting temperature. This is crucial for capturing the local material structure after processes introducing highly localized deformation such as mechanical joining processes between metal and fiber reinforced thermoplastics (FRTP). A generic finite element (FE) model is developed, incorporating interfaces discretized through either cohesive zone (CZ) elements or Coulomb friction-based contacts. The material parameters for the FE elements are derived from the initial stiffness of a statistical volume element (SVE) at micro scale modelled with an Arbitrary-Lagrange-Eulerian method for three load cases. The CZ properties calculated are based on the shear viscosity of the composite. The CZ and contact modelling approaches are evaluated using three load cases of the SVE, comparing force-displacement curves. Under simple loading conditions, such as normal pressure tension and bending, both methods produce similar results; however, in complex load cases, the CZ approach shows clear advantages in handling interface interactions and shows robust simulations. The CZ approach thus presents a promising method for simulating roving decomposition in FRTP-metal joining applications above the matrix{’} melting temperature.
Keywords: Finite Element Method (FEM); Process; Thermoplastic Fiber Reinforced Plastic

Efficient failure information propagation under complex stress states in fiber reinforced polymers: From micro- to meso-scale using machine learning - Gerritzen, Johannes; Hornig, Andreas; Gude, Maik (Sheet Metal 2025)
The failure behavior of fiber reinforced polymers (FRP) is strongly influenced by their microstructure, i.e. fiber arrangement or local fiber volume content. However, this information cannot be directly used for structural analyses, since it requires a discretization on micrometer level. Therefore, current failure theories do not directly account for such effects, but describe the behavior averaged over an entire specimen. This foundation in experimentally accessible loading conditions leads to purely theory based extension to more complex stress states without direct validation possibilities. This work aims at leveraging micro-scale simulations to obtain failure information under arbitrary loading conditions. The results are propagated to the meso-scale, enabling efficient structural analyses, by means of machine learning (ML). It is shown that the ML model is capable of correctly assessing previously unseen stress states and therefore poses an efficient tool of exploiting information from the micro-scale in larger simulations.
Keywords: Failure; Fiber Reinforced Plastic; Machine Learning

3D viscoelastic plastic model coupled with a continuum damage formulation for fiber reinforced polymers - Gerritzen, Johannes; Gröger, Benjamin; Zscheyge, Matthias; Hornig, Andreas; Gude, Maik (Materials & Design)

Manifold of mappings and regularity properties of half-Lie groups - Pinaud, Matthieu

Quality assurance of clinched joints using explainable machine learning - Gerritzen, Johannes; Chopra, Kunal; Reschke, Gregor; Hornig, Andreas; Brosius, Alexander; Gude, Maik (Journal of Advanced Joining Processes)